How to Improve Cord Blood Engraftment? - Beksac, Meral; Yurdakul, Pinar (Frontiers in Medicine, 2016)
Various factors make cord blood (CB) a significant source of hematopoietic stem cells (HSC), including ease of procurement and lack of donor attrition, with the ability to process and store the donor cells long term. Importantly, high proliferative potential of the immature HSCs allows one log less use of cells compared to bone marrow (BM) or peripheral blood stem cells. As total nucleated cell (TNC) and CD34 + cell content of CB grafts are correlated with engraftment rate and speed, strategies to expand HSC and homing have been developed. This chapter will focus on modalities such as intra-bone administration, fucosylation, CD26 inhibition, Prostaglandin G2 derivative or complement 3 exposure and SDF-1/CXCR4/CXCL-12 pathway interventions that have been experimented successfully. Furthermore increasing evidence in line with better recognition of CB progenitors that are involved in engraftment and homing will also be addressed.